2015
DOI: 10.1590/s0004-28032015000200012
|View full text |Cite
|
Sign up to set email alerts
|

HELICOBACTER PYLORI PREVALENCE IN PATIENTS WITH CELIAC DISEASE: results from a cross-sectional study

Abstract: Helicobacter pylori infection seems to be less frequent in celiac patients; among those celiac subjects with concomitant Helicobacter pylori infection, histological damage degree and presence of endoscopic markers suggesting villous atrophy seem to be similar to those without Helicobacter pylori infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 20 publications
4
10
0
5
Order By: Relevance
“…It has been established that Hp infection causes duodenitis and induces intra‐epithelial lymphocytosis, whereby Hp infection may contribute to more severe damage in patients with CD. In this study, the histologic severity of duodenal lesions was not influenced by the presence of Hp infection, and it was comparable to the previous publications 12,21,30 . However, there are studies demonstrating milder inflammation in the duodenum of celiac patients when there was a concomitant Hp infection.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…It has been established that Hp infection causes duodenitis and induces intra‐epithelial lymphocytosis, whereby Hp infection may contribute to more severe damage in patients with CD. In this study, the histologic severity of duodenal lesions was not influenced by the presence of Hp infection, and it was comparable to the previous publications 12,21,30 . However, there are studies demonstrating milder inflammation in the duodenum of celiac patients when there was a concomitant Hp infection.…”
Section: Discussionsupporting
confidence: 90%
“…The relationship between CD and Hp infection has been studied previously; however, the results were either contradictory or inconclusive 11,13,20‐23 . Studies done in adults reported that the rate of Hp infection varied between 12.5%‐20.7% in celiac patients, compared with 30%‐55.3% in the dyspeptic adults who had been examined by endoscopy and histopathology 10,12 . Our findings in this study were comparable to those, and the rates of Hp infection were 26.3% vs. 50.1% in CD and controls, respectively.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Celijakija se nekada može javiti udruženo sa drugim oboljenjima kao što su: dermatitis herpetiformis -Duhring, insulin zavisni dijabetes melitus (IDDM), hipotireoidizmom, Daunov i Tarnerov sindrom ili mikroskopski kolitis (6,8,10). U želucu, kod pacijenata sa celijakijom, može se udruženo naći limfocitni gastritis (LG) dok rezultati istraživanja sugerišu manju učestalost hroničnog Helicobacter pylori (Hp) pozitivnog gastritisa (11,12).…”
Section: Uvodunclassified